Looking at-- Troodon : a dinosaur from the Cretaceous period - Anthony, Laurence. frey50; Gibbons, Tony (Milwaukee : Garth Stevens publishing, 1997)
Describes the physical characteristics and probable behavior of this slight, swift carnivore of the Late Cretaceous.
Includes index.
Keywords: Troodon -- Juvenile literature; Troodon; Dinosaurs